No Viral Spreading After Rotavirus Vaccination in NICU. (4th October 2017) - Hiramatsu, Hiroyuki; Suzuki, Ryota; Yamada, Shigeki; Ihira, Masaru; Nagatani, Arisa; Miyata, Masafumi; Miura, Hiroki; Hattori, Fumihiko; Sugata, Ken; Taniguchi, Koki; Nishimura, Naoko; Ozaki, Takao; et al.
Abstract: Background: Preterm and low birth weight infants are considered to be high risk for severe rotavirus gastroenteritis. However, it has been demonstrated that many infants are ineligible for receiving rotavirus vaccine due to over the age limitation within the neonatal intensive care unit (NICU). We sought to elucidate the safety of rotavirus (RV) vaccination in NICU by assessing vaccine virus transmission from vaccine recipients in NICU. Methods: This study was designed as the prospective study conducted at the NICU of Fujita Health University hospital and Konan Kosei Hospital. This study was approved by the ethical committee in our university. Premature age-eligible infants were recruited to administer rotavirus vaccine. Stool samples were serially collected from unvaccinated infants (UVI) and vaccinated infants (VI) who received either the pentavalent rotavirus vaccine (RV5) or monovalent rotavirus vaccine (RV1). During October 10, 2014 and December 25, 2015, 19 VIs and 49 UVIs were enrolled in this study. Contact precaution was carried out in NICU. All stool samples were analyzed by real-time RT-PCR for detection of RV5, RV1, and wild-type strain's genomes. Results: Total of 676 stool samples (89 samples collected from the 9 RV5 vaccinated infants, 110 samples collected from the 10 RV1 vaccinated infants, and 477 samples collected from the 49 UVIs) were analyzed in this study. Nineteen VIs received with first dose of vaccine demonstrated persistent shedding of rotavirus vaccine genome during 1–8 days after the first dose of the vaccine. Meanwhile, in comparison to VIs received with first dose of vaccine, the detection of viral genome in stool samples decreased gradually in there VIs after second dose of vaccine. In contrast to the VI, no vaccine genome was detected in any of the stool samples collected from the UVIs. Conclusion: This study suggests that RV vaccine may be safe for administration of preterm and low birth weight infants in NICU. Accordingly, the contact precaution measures may play an important role in prevention of vaccine virus transmission between VIs and UVIs. Disclosures: All authors: No reported disclosures.